Exploring suicide-related disclosure motivation and the impact on mechanisms linked to suicide. Issue 9 (21st October 2019) - Fulginiti, Anthony; Frey, Laura M.
Abstract: Suicide-related disclosure enables improved risk management but disclosure motivations are understudied. This study identified reasons for and against disclosing suicidal thoughts and examined their link to future disclosure and interpersonal needs among 44 people receiving psychiatric care. The most endorsed reasons for disclosure (approach-motivations) included help-seeking, shared background, and catharsis. The most endorsed reasons against disclosure (avoidance-motivations) included fear of rejection, shame, and hospitalization. Higher mean approach motivation was associated with more disclosure intent and less burdensomeness. No associations with avoidance motivation were observed. Programming that seeks to orient people toward approach motivation holds promise for attenuating suicide risk.